2016
DOI: 10.20944/preprints201608.0195.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Current Understanding on Tail Regeneration in Green Anoles (Anolis carolinensis)

Abstract: Regeneration of lost tail is of great importance to lizards. Anolis carolinensis, a green lizard, is capable of regenerating its tail efficiently after autotomy. Hence, it is considered as a model organism in regeneration study. A. carolinensis shed its tail in order to distract the predator's attention and thus makes a way to escape. Restoring of the amputated tail takes several days and the mechanism is currently clearly understood. Although save its life, tail regeneration is associated with the impairment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The expression pattern of each gene was different depending on the growth factor added. Nain et al [ 29 ] have reported that ACAN , COL9A1 , and COL2A1 genes are involved in cell adhesion and skeletal system development during myogenesis. In addition, ACAN is also a cartilage specific matrix protein.…”
Section: Discussionmentioning
confidence: 99%
“…The expression pattern of each gene was different depending on the growth factor added. Nain et al [ 29 ] have reported that ACAN , COL9A1 , and COL2A1 genes are involved in cell adhesion and skeletal system development during myogenesis. In addition, ACAN is also a cartilage specific matrix protein.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, tail regeneration activates numerous genes of development (Hutchins et al, 2014; Vitulo et al, 2017a, 2017b), forms a blastema rich in hyaluronic acid and water, large tissues such segmented muscle, a long axial skeleton, long nerves and vessels, large scales, and large adipomeres with numerous fat cells. A long list of past publications on the microscopic events of tail regeneration in different species of lizards is reported in Bellairs and Bryant (1985) and in Alibardi (1995, 2010, 2014a, 2017a), and additional information can be found in other recent papers (Chung, 2016; Fisher et al, 2012; Gilbert & Vickaryous, 2018; Gilbert, Payne, & Vickaryous, 2013; Lozito & Tuan, 2015, 2016a, 2016b; Nain, 2016). The cells contributing to the formation of the regenerative blastema and the new spinal cord appears from local dedifferentiation and also from putative stem cells present in various tissues of the tail stump (Alibardi, 2015a, 2016b, 2017e; Londono, Wenzhong, Wang, Tuan, & Lozito, 2017).…”
Section: Lizard Regeneration Shows the Limitations Of Morphogenesis Imentioning
confidence: 72%
“…The expression pattern of each gene was different depending on the growth factor added. Nain et al [29] have reported that ACAN, COL9A1, and COL2A1 genes are involved in cell adhesion and skeletal system development during myogenesis. ACAN is also a cartilage speci c matrix protein.…”
Section: Discussionmentioning
confidence: 99%